2005
DOI: 10.1093/humrep/dei268
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of ovarian function after orthotopic (intraovarian and periovarian) transplantation of cryopreserved ovarian tissue in a woman treated by bone marrow transplantation for sickle cell anaemia: Case report

Abstract: Ovarian function after orthotopic transplantation of cryopreserved ovarian tissue has been restored in women with malignant disease. Here the techniques are adapted for a non-cancer patient. In 1999, right oophorectomy was performed in a 21 year old woman before chemotherapy, prior to bone marrow transplantation. Ovarian cortex was frozen, according to a strict protocol. After thawing, ovarian cortex was reimplanted into the ovary and in a peritoneal window close to the ovary in 2004. Four-and-a-half months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(80 citation statements)
references
References 28 publications
3
71
0
6
Order By: Relevance
“…Israely et al [28] reported that implantation of ovarian graft into an angiogenic granulation tissue, created during wound healing, improved graft vascularization and follicular survival. Based on these results, this physiologic phenomenon was successfully applied for autotransplantation in women inducing new blood vessel formation by creating a peritoneal pocket or longitudinal opening of the ovary at the ovarian tissue transplantation sites 1 week before the transplantation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Israely et al [28] reported that implantation of ovarian graft into an angiogenic granulation tissue, created during wound healing, improved graft vascularization and follicular survival. Based on these results, this physiologic phenomenon was successfully applied for autotransplantation in women inducing new blood vessel formation by creating a peritoneal pocket or longitudinal opening of the ovary at the ovarian tissue transplantation sites 1 week before the transplantation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…While overall fertility is preserved in the majority of women with SLE (Park et al 2004), they require variable treatment dosages over a more prolonged period than malignancies, adding to the difficulties of patient selection. Other appropriate conditions may include sickle cell disease where treatment with total body irradiation (TBI) is proposed (Donnez et al 2006a). The present data highlight the mortality associated with these non-malignant conditions.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…O restabelecimento de função ovariana pós-reimplante de tecido ovariano congelado-descongelado já foi descrito por alguns autores [23][24][25] , inclusive com nascimento de criança sadia após falência ovariana pós-quimioterapia comprovada, seja por gestação espontânea 26,27 ou por técnicas de reprodução assistida 28 . A conservação do tecido em si a partir de técnicas de congelamento não é tão complicada.…”
Section: Criopreservação De Oócitosunclassified
“…A maior difi culdade está no período pós-reimplante imediato, quando o risco de isquemia é maior e conseqüentemente há perda folicular irreversível 30 . Por isso a técnica de reimplante adotada parece ser o ponto principal, e alguns autores sugerem o uso de tiras de córtex reimplantados sobre o ovário atrófi co 23 , outros sugerem implantação subperitoneal na fossa ovárica através da criação de "bolsão" 25,26,31 , ou ainda do córtex ovariano inteiro sobre a medula residual 32 . Todos apresentam bons resultados, porém com pequenas casuísticas.…”
Section: Criopreservação De Oócitosunclassified